2018
DOI: 10.1126/scitranslmed.aan1230
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ inhibition restores a regenerative response in acute liver injury by suppressing paracrine senescence

Abstract: One Sentence Summary:Inhibiting injury-induced senescence mediated by TGFβ signaling in regenerative epithelium improves liver regeneration. Accessible Summary:The liver is a paradigm of organ regeneration, however regeneration may fail in a previously normal liver following acute severe injury such as acetaminophen poisoning. We show that, a process with prevents proliferation termed senescence, which is classically associated with aging and carcinogenesis, stops the liver's regenerative cells. This senescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
207
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(238 citation statements)
references
References 60 publications
13
207
2
Order By: Relevance
“…In this model, the presence of p53 induction through Mdm2 deletion with 15 medium levels of CDKN1A (non senescence/primary p<0.001) marks primary senescence induction (34) (Fig.4b, Supplementary Fig.4a,b). Physiological levels of p53 and high levels of CDKN1A (CDKN1A expression secondary/primary p<0.0001) marks secondary senescence in Mdm2 normal (Mdm2+) hepatocytes as described (34) (Fig. 4b).…”
Section: Ratio Of Enrichment Of Over-representation Pathway Analysismentioning
confidence: 80%
See 2 more Smart Citations
“…In this model, the presence of p53 induction through Mdm2 deletion with 15 medium levels of CDKN1A (non senescence/primary p<0.001) marks primary senescence induction (34) (Fig.4b, Supplementary Fig.4a,b). Physiological levels of p53 and high levels of CDKN1A (CDKN1A expression secondary/primary p<0.0001) marks secondary senescence in Mdm2 normal (Mdm2+) hepatocytes as described (34) (Fig. 4b).…”
Section: Ratio Of Enrichment Of Over-representation Pathway Analysismentioning
confidence: 80%
“…Based on these characteristics, cells can be readily distinguished by immunohistochemistry with 23% of primary and 10% of 20 secondary senescence hepatocytes detected ( Supplementary Fig.4a). We have previously shown that both subpopulations of hepatocytes upregulate senescence markers (gH2AX, IL1A, SA-beta Galactosidase) and reduce BrdU incorporation (34).…”
Section: Ratio Of Enrichment Of Over-representation Pathway Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in models of liver fibrosis induced by CCl4 treatment, a robust senescence response is induced primarily in the stellate cells, which serves to limit fibrosis (Krizhanovsky et al, 2008). Other models of severe liver damage such as extended hepatectomy (Lehmann et al, 2012), acetaminophen treatment (Bird et al, 2018), Mdm2-deletion (Lu et al, 2015), b1-integrin loss ( (Raven et al, 2017) or p21-overexpression (Raven et al, 2017), each induce a pronounced p21expression in hepatocytes, which results in decreased regeneration, senescence, and senescence-spreading. It will be interesting to determine if senolytic-treatment can also improve such cases of severe damage.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular senescence has fundamental roles in organismal ageing, age‐related diseases, tumourigenesis and tissue regeneration . There are three major types of cellular senescence: (a) replicative senescence, (b) oncogene‐induced senescence and (c) DNA damage‐induced senescence.…”
Section: Introductionmentioning
confidence: 99%